Tokophrya Niphargi (Ciliophora, Suctoria) — второе обнаружение троглобионтной суктории и переописание вида - Довгаль, И.В. (Вестник зоологии, 1993)
A redescription of Tokophrya niphargi (Si rouhal), com!), n. found in Iphigenella shablensis from an underground spring in the Ukrainian Carpathians The author of the original description erroneously accepted different individuals of the species, seen under‘different aspects, as belonging to two species of different genera.